Immune dysregulation in Kabuki syndrome: a case report of Evans syndrome and hypogammaglobulinemia - Leonardi, Lucia; Testa, Alessia; Feleppa, Mariavittoria; Paparella, Roberto; Conti, Francesca; Marzollo, Antonio; Spalice, Alberto; Giona, Fiorina; Gnazzo, Maria; Andreoli, Gian Marco; Costantino, Francesco; Tarani, Luigi (Frontiers in Pediatrics, 2023)
Kabuki syndrome (KS) is a rare multisystemic disease due to mutations in the KMT2D or KDM6A genes, which act as epigenetic modulators of different processes, including immune response. The syndrome is characterized by anomalies in multiple organ systems, and it is associated with autoimmune and inflammatory disorders, and an underlying immunological phenotype characterized by immunodeficiency and immune dysregulation. Up to 17% of KS patients present with immune thrombocytopenia characterized by a severe, chronic or relapsing course, and often associated to other hematological autoimmune diseases including autoimmune hemolytic anemia, eventually resulting in Evans syndrome (ES). A 23-year-old woman, clinically diagnosed with KS and presenting from the age of 3 years with ES was referred to the Rare Diseases Centre of our Pediatric Department for corticosteroid-induced hyperglycemia. Several ES relapses and recurrent respiratory infections in the previous years were reported. Severe hypogammaglobulinemia, splenomegaly and signs of chronic lung inflammation were diagnosed only at the time of our observation. Supportive treatment with amoxicillin-clavulanate prophylaxis and recombinant human hyaluronidase-facilitated subcutaneous immunoglobulin replacement were immediately started. In KS patients, failure of B-cell development and lack of autoreactive immune cells suppression lead to immunodeficiency and autoimmunity that may be undiagnosed for a long time. Our patient’s case is paradigmatic since she presented with preventable morbidity and severe lung disease years after disease onset. This case emphasizes the importance of suspecting immune dysregulation in KS. Pathogenesis and immunological complications of KS are discussed. Moreover, the need to perform immunologic evaluations is highlighted both at the time of KS diagnosis and during disease follow-up, in order to allow proper treatment while intercepting avoidable morbidity in these patients.